The effects of cognitive information processing and social cognitive career group counseling on high school students’ career adaptability - Wang, Danqi; Liu, Xiping (Frontiers in Psychology, 2022)
The aim of this study was to examine the effect of cognitive information processing(CIP) and social cognitive career theory(SCCT) group counseling on high students’ career adaptability. The study involved 81 students from grade 10 and grade 11 in a Chinese public high school. Among the 81 participants, 27 were in the CIP group, 28 were in the SCCT group, while the rest were in the control group. All participants completed a pre-test, post-test, and tracking test assessment of their career adaptability. Results indicated that the interventions were effective for the students with low career adaptability, the CIP group counseling improved the career concern after the intervention, whereas the SCCT group revealed a more robust effect on career adaptability after three months of the intervention. The practical implications of the study for career interventions are also discussed.